Chemical constituents of Ligularia alticola Worosch. leaves and their biological activities. (March 2016) - Ponomarenko, Ludmila P.; Kalinovsky, Anatoly I.; Berdyshev, Dmitrii V.; Kuzmich, Alexandra S.; Menchinskaya, Ekaterina S.; Pislyagin, Evgeny A.; Kim, Natalia Yu.; Glazunov, Valery P.; Dmitrenok, Pavel S.; Silchenko, Alexandra S.; Avilov, Sergey A.; Gorovoy, Peter G.; et al.
Graphical abstract: Highlights: Seven sesquiterpenes and seven triterpenes were obtained from Ligularia alticola . This is the first report of the isolation of 3α-cylcoartanols from the Asteraceae family. TD-DFT and NMR-GIAO methods were employed to clarify the structure of compound1 . Compound 2 was cytotoxic against HL-60 and Raji cells. Abstract: Seven eremophilane-type sesquiterpenes (1–7 ), six cycloartane derivatives (8 –13 ) and α-amyrin acetate (14 ) were isolated from the leaves of the far-eastern plant Ligularia alticola Worosch. (Family Asteraceae). (4 S, 5 R, 8 S, 10 R )-8-Ethoxyeremophil-7(11)-en-12(8)-olide (1 ), 8α, 11-epidioxy-8β-methoxyeremophil-6-ene (2 ) and 29-norcycloartan-3α-ol (8 ) have not been previously reported. Fukinone α-epoxide (3 ) was isolated for the first time from a natural source. The structures of all the compounds were established by the extensive analysis of their 1D and 2D NMR spectra and HR ESI mass spectrometry. The absolute stereochemistry of1 was determined by comparison of theoretical and experimental ECD spectra with the application of B3LYP-TDDFT and B3LYP-GIAO calculations as well as by NMR spectroscopy. Compound1 showed cytotoxic action against human cancer HL-60, Raji, and THP-1 cell lines (IC50 12.6, 6.0 and 6.9 μM, respectively). Compounds2 and4 demonstrated significant cytotoxic activities against HL-60 (IC50 2.8 and 5.8 μM, respectively) and Raji cells (IC50 2.9 and 4.2 μM, respectively). Compound6 was cytotoxic against Raji cells (IC50 4.6 μM). None of tested compounds were cytotoxic against RAW 264.7 cells. Compounds1 and4–7 significantly decreased intracellular ROS levels, induced by endotoxic LPS from Escherichia coli in RAW 264.7 murine macrophages.